Soviet economic aid : the new aid and trade policy in underdeveloped countries - Berliner, Joseph S. (New York : Published for the Council on Foreign Relations by F. A. Praeger, 1958)
The book examines economic aid provided by the Soviet Union and trade policy in underdeveloped countries. Topics covered includes: the politics of economic aid; the character and size of the aid programme; soviet aid and western aid; the expansion of commercial trade, soviet capacity to extend economic aid, soviet economic gains from the aid program; and Greek bearing gifts?
Includes index.
Includes bibliographical references: p. 224-228.
lje 07/05/2018
Loans
Keywords: Economic assistance, Soviet; Technical assistance, Soviet; Soviet Union